GLOBALISASI DAN RESPON PESANTREN - Qolbi Khoiri (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2019)
Th e purpose of writing this article is to explain the phenomenon of globalization from its understanding of the shape and impact of globalization which then impacts Islamic boarding schools and how Islamic boarding schools respond to them. Analysis of this article is done using a literature study. Th e results of the analysis found that Islamic boarding schools view globalization as an age dynamic that cannot be avoided. Th erefore, pesantren choose to be active while maintaining the identity and characteristics of the pesantren that function as a pioneer of reform (agent of change). Th e impact of globalization faced by pesantren must be made with several changes, namely changes in infrastructure and physical buildings of Islamic boarding schools. Changes involve the management and management of Islamic boarding schools. Changes in the widening of the scope and level of education in pesantren. Changes in the way the pesantren behave are no longer closed. Changes in boarding schools in the face of change will not be successful without a positive attitude from the government.